A Continuous Millimeter-Wave Imaging Scanner for Art Conservation Science. (23rd November 2011) - Younus, Ayesha; Caumes, Jean-Pascal; Salort, Simon; Chassagne, Bruno; Pradère, Christophe; Dautant, Alain; Ziéglé, Anne; Abraham, Emmanuel
Abstract : A monochromatic continuous millimeter-wave imaging system coupled with an infrared temperature sensor has been used to investigate artistic objects such as painting artworks or antiquities preserved at the museum of Aquitaine. Especially, 2D and 3D analyses have been performed in order to reveal the internal structure of a nearly 3500-year-old sealed Egyptian jar.